Peningkatan Performa Induk dan Uji Penggunaan Ekstrak Daun Teh (Camelia Sinensis) Terhadap Keberhasilan Penetasan Telur Ikan Semah (Tor Duoronensis) - Ghofur, Muarofah; Syahrizal, Syahrizal; Yusuf, Noor Syarifuddin; Hudaiya, Wilham; Saparuddin, Baso' Muhammad (Universitas Batangahari Jambi, 2026)
Semah fish (Tor douronensis) is one of the endemic fish species with high economic value. However, the hatch rate of Semah fish eggs is still low due to contamination from waste and fungi. Washing the eggs with natural materials has been used to improve hatching success in various fish species, and one of the natural materials used is tea leaves because they contain tannins and flavonoids that can inhibit bacterial and fungal attacks. The purpose of this study is to determine the effectiveness of using tea leaf extract (Camelia sinensis) on the hatching success of Semah fish eggs (Tor douronensis) at an optimal dosage. This study will use a completely randomized design (CRD) with 4 treatments and 3 replications, namely: Treatment A) Tea leaf extract concentration 0.4 ml/L, Treatment B) Tea leaf extract concentration 0.6 ml/L, Treatment C) Tea leaf extract concentration 0.8 ml/L, and Treatment D) Tea leaf extract concentration 0 ml/L (Control). The research results, which have been conducted and analyzed descriptively regarding the injection of hCG three times over a 30-day maintenance period, show an effect on the gonad maturity index with an average value of 6.70%. The egg hatchability is 0.8 ml/L with a success rate of 89.67%, and it results in the largest egg diameter distribution ranging from 1.8 to 2.4 mm.